2015
DOI: 10.2337/dc14-1598
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Lower-Extremity Amputation in Patients With an Infected Diabetic Foot Ulcer

Abstract: OBJECTIVEInfection commonly complicates diabetic foot ulcers and is associated with a poor outcome. In a cohort of individuals with an infected diabetic foot ulcer, we aimed to determine independent predictors of lower-extremity amputation and the predictive value for amputation of the International Working Group on the Diabetic Foot (IWGDF) classification system and to develop a risk score for predicting amputation. RESEARCH DESIGN AND METHODSWe prospectively studied 575 patients with an infected diabetic foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
157
3
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(172 citation statements)
references
References 30 publications
6
157
3
6
Order By: Relevance
“…23 In diabetics, local infections, with plantar ulcers, edema, and hyperemia, are known high-risk factors for amputations. 8,24 However, the present study observed that only sepsis was related to major amputations, irrespective of the presence of local infection. In these cases, the importance of taking a treatment decision immediately to prevent progression to septic shock and death cannot be overstated.…”
Section: 15contrasting
confidence: 45%
“…23 In diabetics, local infections, with plantar ulcers, edema, and hyperemia, are known high-risk factors for amputations. 8,24 However, the present study observed that only sepsis was related to major amputations, irrespective of the presence of local infection. In these cases, the importance of taking a treatment decision immediately to prevent progression to septic shock and death cannot be overstated.…”
Section: 15contrasting
confidence: 45%
“…20 In a multi centre study from Europe, infection was confirmed to be a major contri buting factor to lower extremity amputation in patients with diabetes mellitus; markers of severity of infection, such as periwound oedema, foul smell and raised Cprotein levels, were all found to independently predict amputation. 21 In a study from Iran of patients with diabetes mellitus who presented with foot infections, 45% of participants required local or major amputation. 22 Amputations also frequently result from diabetic foot problems in Asia, and several of the Caribbean islands have some of the highest amputation rates in the world.…”
Section: Epidemiologymentioning
confidence: 99%
“…Con base en los hallados, los investigadores desarrollaron nuevos puntajes que no son contemplados por el sistema de clasificación por el IWGDF que pueden ser fácilmente empleados en la práctica clínica (13) .…”
Section: Enfermería Globalunclassified